Effectiveness of atraumatic restorative treatment, Hall Technique and conventional restoration using resin or amalgam after 18 months of follow-up: a randomized controlled trial (Research, Society and Development, 2020)
There are different options for restorations of deciduous teeth.  The aim of this study was to evaluate the success rate of conventional and atraumatic restorations, Class I and Class II lesions in primary molars. This is a randomized controlled trial in Olinda, Brazil. The control groups were the conventional restorations with resin (205) and amalgam (198), and the case groups were atraumatic approaches with the ART (211) and the Hall technique (117). A total of 731 restorations were performed in a dental office setting in 731 children (4- to 8-year-olds). All the restorations were evaluated after 6, 12 and 18 months. The survival rate of Class I restorations was higher (> 85% success) for all restorations compared to Class II (16.9%-99.1%, success/minor failure). The success rates of Class II restorations after 18 months were not satisfactory for conventional restorations with resin (16.9%, success/minor failure) and ART (31%, success/minor failure), while were satisfactory for conventional restorations with amalgam (70,3%, success), and outstanding for Hall technique (99,1%, success). The success rate for Class I was higher than II for all restorations. Considering Class II, the success rate was low for ART and conventional restorations with resin, satisfactory for amalgam, and excellent for Hall Technique.